Evidence for localisation of accumulated chlorophyll cation on the D1-accessory chlorophyll in the reaction centre of photosystem II - Vacha, Frantisek; Psencik, Jakub; Kuty, Michal; Durchan, Milan; Siffel, Pavel (Photosynthesis research, 2005)
Absorption and circular dichroism spectra of Photosystem II (PS II) reaction centres (RC) were studied and compared with spectra calculated on the basis of point-dipole approximation. Chlorophyll cation was accumulated during a light treatment of PS II RC in the presence of artificial electron acceptor silicomolybdate. Light-induced difference spectra and their calculated counterparts revealed the location of accumulated cation at the accessory chlorophyll of the D1 protein subunit.
Keywords: Spectrophotometry, Atomic; biologické modely; hrách setý; kationty; teplota; Pisum sativum; Cations; Energy Transfer; Plant Proteins; Models, Biological; Photosystem II Protein Complex; fotosystém II (proteinový komplex); chlorofyl; přenos energie; rostlinné proteiny; spektrofotometrie atomová; Light; Temperature; Circular Dichroism; světlo; Chlorophyll; cirkulární dichroismus